2023
DOI: 10.3390/nu15132928
|View full text |Cite
|
Sign up to set email alerts
|

Bean Leaves Ameliorate Lipotoxicity in Fatty Liver Disease

Abstract: Bioactive compounds in plant-based food have protective effects against metabolic alterations, including non-alcoholic fatty liver disease (NAFLD). Bean leaves are widely cultivated in the world and are a source of dietary fiber and polyphenols. High fat/high fructose diet animal models promote deleterious effects in adipose and non-adipose tissues (lipotoxicity), leading to obesity and its comorbidities. Short-term supplementation of bean leaves exhibited anti-diabetic, anti-hyperlipidemic, and anti-obesity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Interestingly, the reduction in adipose tissue due to BL consumption can be attributed to the contribution of phenolic compounds (r = −0.451). Similarly, it was previously reported that the consumption of bean leaves in rats on an obesogenic diet prevents weight gain and the amount of adipose tissue without decreasing energy consumption [11,13].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Interestingly, the reduction in adipose tissue due to BL consumption can be attributed to the contribution of phenolic compounds (r = −0.451). Similarly, it was previously reported that the consumption of bean leaves in rats on an obesogenic diet prevents weight gain and the amount of adipose tissue without decreasing energy consumption [11,13].…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, the improvement in metabolic alterations is related to the significantly higher concentration of short-chain fatty acids (SCFAs, 54%) in the cecal content [11]. In another study, supplementation with bean leaves of the Eugenia variety for 13 weeks prevented hepatic lipotoxicity in rats fed HFFD [13]. Therefore, these results led us to suggest that a strategy to reduce obesity is to improve intestinal integrity through bean leaves consumption.…”
Section: Introductionmentioning
confidence: 97%
“…Li et al explored the therapeutic effects of diet in MASLD patients and determined that intermittent fasting (IF) was more beneficial in reducing the lipotoxicity of MASLD compared to conventional therapies than switching to a normal diet (ND) [ 140 ]. Recently, a high-fat/high-fructose diet including 10% of bean leaves has also been found to ameliorate lipoatrophy and lipid peroxidation in fatty liver disease, providing new perspectives for the prevention and treatment of MASLD and MASH [ 141 ]. Regular exercise may also alleviate glycolipid metabolism disorders and thus be effective against MASLD, but there is no clear evidence regarding the therapeutic effects of exercise modalities in patients with MASLD in the literature [ 142 , 143 ].…”
Section: Research Prospects For Therapeutic Strategiesmentioning
confidence: 99%